2023
DOI: 10.47440/jafe.2023.4103
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of combined effect of Eleocharis atropurpurea and Fimbristylis dichotoma residues on the yield performance of T. aman rice

Abstract: The current agricultural system is seeking a biological solution to lesson hazardous impacts from the use of chemicals to control weeds in rice production. Plant allelopathy is one of the ways where allelopathic plant inhibits its surrounding plants by releasing allelopathic substances. The present experiment was conducted at the Agronomy Field Laboratory, Bangladesh Agricultural University, Mymensingh during the period from July to December 2019 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 13 publications
0
0
0
Order By: Relevance
“…It might be due to application of residues added organic matter to the soil and enhance grain yield. Farhat et al (2023) [8] ; Uddin and Pyon (2010) [31] also reported the similar results, where residues influenced in crop performance. Straw yield was significantly influenced by the residues of Fimbristylis dichotoma.…”
Section: Yield and Yield Contributing Characters At Harvest Effect Of...mentioning
confidence: 62%
“…It might be due to application of residues added organic matter to the soil and enhance grain yield. Farhat et al (2023) [8] ; Uddin and Pyon (2010) [31] also reported the similar results, where residues influenced in crop performance. Straw yield was significantly influenced by the residues of Fimbristylis dichotoma.…”
Section: Yield and Yield Contributing Characters At Harvest Effect Of...mentioning
confidence: 62%